Equilibrium and stability of cylinder plasma consisting of unmagnetized ions been born at rest and magnetized electrons in crossed fields - Yeliseyev, Yu.N. (Вопросы атомной науки и техники, 2006)
The equilibrium and the non-local stability problem of cylinder plasma, consisting of magnetized electrons and unmagnetized ions, having been born at rest under the ionization of the residual gas, are considered. The equilibrium distribution function of such ions is used. The dispersion equation of eigen helical plasma waves is obtained analytically and solved numerically for various azimuth wave numbers. For the lowest radial modes the instability of «negative mass»-type is possible having the frequency of the order of ion radial oscillation one and the growth rate up to 0.5 of it.